2021
DOI: 10.1186/s40594-021-00302-2
|View full text |Cite
|
Sign up to set email alerts
|

Active learning through flipped classroom in mechanical engineering: improving students’ perception of learning and performance

Abstract: Background To address some challenges that the large lecture-focused courses have faced in higher education, the flipped classroom model was implemented in mechanical engineering. The purpose of the study was to investigate mechanical engineering undergraduate students’ performance in the flipped classroom. A comprehensive analysis was conducted to investigate the pedagogical benefits of active learning in the flipped classroom from a self-determination theory perspective. To evaluate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 48 publications
5
39
0
1
Order By: Relevance
“…The homogeneity of the faculty’s responses across different general characteristics (gender, academic rank, degree, and discipline) was assessed by ANOVA and Levene’s tests [ 39 , 40 ]. The student’s and faculty’s written comments were subjected to qualitative content analysis to find common themes among the perceptions [ 41 ]. The reliability (internal consistency) of the surveys was assessed through Cronbach’s alpha (α) value.…”
Section: Methodsmentioning
confidence: 99%
“…The homogeneity of the faculty’s responses across different general characteristics (gender, academic rank, degree, and discipline) was assessed by ANOVA and Levene’s tests [ 39 , 40 ]. The student’s and faculty’s written comments were subjected to qualitative content analysis to find common themes among the perceptions [ 41 ]. The reliability (internal consistency) of the surveys was assessed through Cronbach’s alpha (α) value.…”
Section: Methodsmentioning
confidence: 99%
“…Bergmann & Sams (2012); McLaughlin et al, (2014) Beberapa manfaat atau keunggulan metode ini dapat membantu peserta didik lebih berperan aktif dalam mencari dan mengolah belajarnya sendiri. Adapun keunggulan flipped classroom yang dijabarkan oleh Cho et al, (2021) yaitu 1) model flipping dapat menjawab tantangan peserta didik masa kini; 2) membantu peserta didik yang memiliki banyak kegiatan di luar sekolah; 3) membantu peserta didik yang berkeinginan dan berusaha untuk memahami materi belajar; 4) membantu peserta didik untuk menjadi yang terbaik; 5) memungkinkan pendidik memahami karakteristik peserta didik yang lebih baik; 6) meningkatkan interaksi antar peserta didik.…”
Section: Pendahuluanunclassified
“…To assure the users and future users a means through which hybrid learning practices and applications are sustained for long-term educational impact across time, an appropriate plan for the management of hybrid learning practices is needed [18][19][20]. In engineering education, many authors have shown that the appropriation of scientific practices is a sophisticated, cognitive and metacognitive process that demands practice and a certain level of scaffolding [13][14][15][16][17][18][19][20].…”
Section: Recommendationsmentioning
confidence: 99%
“…Moreover, online teaching suits a variety of learning styles, giving options to students with varying intellect to learn in a conducive atmosphere. However, virtual training comes with its own set of challenges such as sense of isolation felt by the students and the instructors alike, lack of continuous focus on the screen, lack of teacher training to handle unprecedented situations and, most importantly, technological issues, which demands very robust background support [13][14][15][16][17].…”
mentioning
confidence: 99%